Reis, Rainhas, Calungas , Balaios e Batuques: imagens no Maracatu Az de Ouro e suas práticas educacionais. - Carneiro, Mário Henrique Thé Mota (2007)
This research deals with the Ace of Gold Maracatu Cultural Association and how this maracatu group-wich is the oldest one of Fortaleza - develops its ways of learning. The main goal of this dissertation paper is to shed a light on how learning process is developed from the deep inside of a maracatu group. It was noticed from the field observation that education is present in some situations called " not formal learning situations" which amount of knowledge is passed on in a very particular and creative way along a never-ending flow of playing and learning. In order to perceive this learning process, it was necessary to dive deep in the symbolic and playful universe of this urban maracatu of Fortaleza. In a zoom perspective, it was observed its daily routine full of cultural presentations where real popular spetacles take place, and common and anonimus people transform themselves into characters that take part along the maracatu procession which is a religious-dramatic dance based upon african cultural background. To know its conflicts and financial difficulties, its ways of sociabilities, its dynamics was something intense and full complexities allowing to infer that it is by playing that we lear to research and it is by researching that we learn to play. In this particular case, to play is dancing maracatu, coloring the face black and beating the drum. All this experiences allowed to perceive, as researcher, that there are ways of building and transmiting knowledge by means of an extremely peculiar cultural practice as it is in the case of the urban Maracatu Ace of Gold.